Relationship between low-density lipoprotein cholesterol and severe acute pancreatitis (“the lipid paradox”) - Hong W; Zimmer V; Stock S; Zippi M; Omoshoro-Jones JAQ; Zhou M (Dove Medical Press, 2018)
Wandong Hong,1,* Vincent Zimmer,2,3,* Simon Stock,4,* Maddalena Zippi,5 Jones AQ Omoshoro-Jones,6 Mengtao Zhou71Department of Gastroenterology and Hepatology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2Department of Medicine II, Saarland University Medical Center, Saarland University, Homburg, Germany; 3Department of Medicine, Marienhausklinik St Josef Kohlhof, Neunkirchen, Germany; 4Department of Surgery, World Mate Emergency Hospital, Battambang, Cambodia; 5Unit of Gastroenterology and Digestive Endoscopy, Sandro Pertini Hospital, Rome, Italy; 6Department of Surgery, Chris Hani-Baragwanath Academic Hospital, University of the Witwatersrand, Johannesburg, South Africa; 7Department of Surgery, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workBackground and aim: The aim of this study was to investigate the association between low-density lipoprotein cholesterol (LDL-C) and the development of severe acute pancreatitis (SAP).Patients and methods: A total of 674 patients with acute pancreatitis were enrolled. Nonlinearity in the relationship between LDL-C and SAP was assessed by restricted cubic spline analysis. Univariable and multivariable regression analyses were used to identify independent risk factors of SAP.Results: The restricted cubic spline analysis suggested a nonlinear association between high-density lipoprotein cholesterol (HDL-C), LDL-C and triglyceride levels and incidence of SAP. The incidence of SAP in patients with low LDL-C (<90 mg/dL), moderate LDL-C (90–150 mg/dL) and high LDL-C (>150 mg/dL) levels was 15.1%, 3.7% and 9.8%, respectively. Multivariable analysis confirmed that low LDL-C levels (odds ratio [OR] 3.05; 95% confidence interval [CI] 1.35–6.90), high LDL-C levels (OR 4.42; 95% CI 1.41–13.87) and low HDL-C levels (OR 6.90; 95% CI 2.61–18.23) but not high triglyceride levels (OR 1.05; 95% CI 0.40–2.72) were associated with the development of SAP.Conclusion: Both low LDL-C (<90 mg/dL) and high LDL-C (>150 mg/dL) levels within 24 hours from admission are independently associated with an increased risk of SAP. Keywords: low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, lipids, acute pancreatitis, severe acute pancreatitis, risk factor